Reproductive Health and Socio-Cultural Factors in Scientific Literature - Efa Nasrun (Health & Medical Sciences, 2026)
This article aims to examine how reproductive health is conceptualized and analyzed within contemporary scientific literature through the lens of socio cultural factors. The study employs a qualitative descriptive research design using a library based approach. Data were collected through systematic literature review and document analysis of recent peer reviewed journal articles that focus on reproductive health and its social, cultural, and normative determinants. The analysis was conducted inductively through thematic identification, data reduction, and conceptual categorization to synthesize patterns and relationships across the reviewed studies. The findings reveal that reproductive health outcomes are consistently shaped by socio cultural norms, gender relations, religious beliefs, and power structures that influence knowledge, access to services, decision making, and reproductive autonomy. Key themes identified include the regulation of adolescent sexual and reproductive health, menstrual health stigma, unmet family planning needs, and the dual role of religion as both a constraint and a source of support. These results indicate a clear shift in the literature from purely biomedical perspectives toward more integrated and context sensitive frameworks. The study concludes that incorporating socio cultural analysis is essential for advancing theoretical understanding and for designing effective, culturally responsive reproductive health interventions. By synthesizing recent scholarly evidence, this article contributes to the development of more comprehensive and socially grounded approaches in reproductive health research and practice.